2012
DOI: 10.1371/journal.pone.0042523
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Ribosomal Protein Gene Introns in Sponges

Abstract: Ribosomal protein genes (RPGs) are a powerful tool for studying intron evolution. They exist in all three domains of life and are much conserved. Accumulating genomic data suggest that RPG introns in many organisms abound with non-protein-coding-RNAs (ncRNAs). These ancient ncRNAs are small nucleolar RNAs (snoRNAs) essential for ribosome assembly. They are also mobile genetic elements and therefore probably important in diversification and enrichment of transcriptomes through various mechanisms such as intron/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The most conserved intron position separates the UBQ from RPS30 domain in FAU and varies from 25 to 3339 bp. The average value of sponge RPG intron length is 164 bp [ 29 ], while human RPGs have significantly longer introns, with the average length of 760 bp [ 30 ]. Transposable element insertions play an important role in the evolution of intron size [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most conserved intron position separates the UBQ from RPS30 domain in FAU and varies from 25 to 3339 bp. The average value of sponge RPG intron length is 164 bp [ 29 ], while human RPGs have significantly longer introns, with the average length of 760 bp [ 30 ]. Transposable element insertions play an important role in the evolution of intron size [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that snoRNAs can change their genomic location within relatively short vertebrate evolutionary time scales [ 35 ]. Since all of examined RPG intron positions were conserved in three Suberites species, it was presumed that on this shorter evolutionary time scale, mobility of snoRNAs is not a significant factor that determines intron dynamics [ 29 ]. However, we found that within the same genus ( Suberites ), SNORA62 can change its genomic location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many ribosomal protein genes (RPGs) have additional extraribosomal functions, being involved in replication, regulation of cell growth, apoptosis, and cancer development [ 58 ]. RPs have shown to be important tools for studying intron evolution, since the analysis of RPG introns in sponges revealed the same rate of conservancy between two different sponge species compared to the conservancy between sponges and humans [ 59 , 60 ]. Since S30 ribosomal protein is produced from the fusion protein transcribed from the pro-apoptotic regulatory gene FAU, its extraribosomal function may be connected to the regulation of apoptosis [ 57 ].…”
Section: Players In Cellular Senescence and Apoptosismentioning
confidence: 99%